Genome Dominance in Allium Hybrids (A. cepa × A. roylei) - Kopecký, David; Scholten, Olga; Majka, Joanna; Burger-Meijer, Karin; Duchoslav, Martin; Bartoš, Jan (Frontiers in Plant Science, 2022)
Genome dominance is a phenomenon in wide hybrids when one of the parental genomes becomes ‘dominant’ while the other genome turns to be ‘submissive’. This dominance may express itself in several ways including homoeologous gene expression bias and modified epigenetic regulation. Moreover, some wide hybrids display unequal retention of parental chromosomes in successive generations. This may hamper employment of wide hybridization in practical breeding due to the potential elimination of introgressed segments from progeny. In onion breeding, A. roylei Stearn. has been frequently used as a source of resistance to downy mildew for cultivars of bulb onion, A. cepa L. This study demonstrates that in A. cepa × A. roleyi hybrids, chromosomes of A. cepa are frequently substituted by those of A. roylei and in just one generation the genomic constitution shifts from 8 A. cepa + 8 A. roylei chromosomes in the F1 generation to the average of 6.7 A. cepa + 9.3 A. roylei in F2. Screening of the backcross generation A. cepa × (A. cepa × A. roylei) revealed that this shift does not appear during male meiosis, which is perfectly regular and results with balanced segregation of parental chromosomes which are equally transmitted to the next generation. This indicates that female meiotic drive is the key factor underlying A. roylei genome dominance. SNP genotyping further suggested that the drive has different strength across the genome, with some chromosome segments displaying Mendelian segregation, while others exhibiting statistically significant deviation from it.